2010
DOI: 10.3109/14767058.2010.501122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal anxiety and music on fetal movements and fetal heart rate patterns

Abstract: NST has anxiogenic effects on mothers and listening to music during the test has positive impact on both maternal and fetal parameters but it is an open question whether maternal anxiety during pregnancy may affect fetal accelerations to such an extent that it could influence clinical judgments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 8 publications
1
29
0
7
Order By: Relevance
“…This positive feedback was due to the prototype stretcher’s convex shape, which adapted to the respiratory diaphragm and allowed free diaphragm extension, which improves oxygenation. The shape promotes physical relaxation, which is important because it reduces maternal anxiety and can have a direct and positive effect on fetal HR patterns 24. All the fetuses in this study maintained baseline fetal HRs with in normal parameters in all the positions the pregnant women assumed on the prototype stretcher.…”
Section: Discussionmentioning
confidence: 60%
“…This positive feedback was due to the prototype stretcher’s convex shape, which adapted to the respiratory diaphragm and allowed free diaphragm extension, which improves oxygenation. The shape promotes physical relaxation, which is important because it reduces maternal anxiety and can have a direct and positive effect on fetal HR patterns 24. All the fetuses in this study maintained baseline fetal HRs with in normal parameters in all the positions the pregnant women assumed on the prototype stretcher.…”
Section: Discussionmentioning
confidence: 60%
“…The Hickey et al study, however, examined trait anxiety in pregnant women and thus does little to demonstrate the STAI's validity in this instance. Furthermore, Faisal-Cury and Menezes cite the STAI's wide use as further rationale, consistent with most of the seven studies who utilised the STAI-S (Coplan et al, 2005;Davis et al, 2004 used the short version, Figueiredo and Costa, 2009;Gourounti et al, 2013;Kafalİ et al, 2011;Loomans et al, 2011;Manjari et al, 2002). Loomans et al for example, state the STAI is frequently used for anxiety in pregnancy yet offer no supporting evidence.…”
Section: Resultsmentioning
confidence: 81%
“…FHR analysis sometimes can be boring and anxiogenic for mother. Kafali et al [21] showed that NST has anxiogenic effects on mothers and listening to music during the test has positive impacts on both maternal and fetal parameters. In the present study, music therapy improved NST parameters.…”
Section: Discussionmentioning
confidence: 99%